Turkey : Gas Sector Strategy - World Bank (Washington, DC, 2014)
The purpose of this note is to assist policymakers by proposing a pragmatic and flexible program of change which will enable Turkey to develop a modernized gas market structure. The note is supportive of the objectives of the natural gas market law and does not call for fundamental changes in it. Rather, it suggests some modification of the law's present rigidities. The context for the note includes several implementation concerns and questions raised by the incumbent gas monopoly, Turkish National Gas Company, government institutions and the private sector.